Senam Kegel - Widjajani, Tri; , Wahyuni, SKM. S.Fis., M.Kes (2016)
Background : Kegel exercises are performed motion exercises as soon as possible after delivery , so that the muscles to stretch during pregnancy and childbirth can return to normal conditions as before. Interest Gymnastics postpartum can restore / enhance the reproductive organs especially the abdominal muscles to the original condition . Repair the abdominal muscle strain / stomach after giving birth , nurture and strengthen the abdominal muscles , pelvic floor muscles , and muscle movement , launched a blood. The reason why the mother after delivery should be doing gymnastics parturition , among others : Because the pelvic floor muscles stretch , abdominal wall muscles slack attitude and body shape change of this research has been done in the graveyard of the pilgrimage through the permissions health polyclinic village Ngudi sane gobayan tomb of Haj Kartasura on 4th april 2015 " . This study uses a pre - experimental design approach One Group Pre and Post Test Design Test to determine the benefits of gymnastics parturition to increase the strength of the abdominal muscles. Samples that meet the inclusion and exclusion criteria amounted to 13 people. Objective: This study aimed to investigate the effect of exercise on muscle strengthening the abdominal postpartum postpartum . Methods: This research method using one-group approach . The study population numbering 13 people . How sampling using purposive sampling method that is performed by inserting each patient who meets the inclusion and exclusion criteria . Results: The data were not normally distributed , using a non-parametric statistical tests . The results of data analysis using the Wilcoxon test showed the value of p = 0.005 < = 0.05 , so that Ho refused and Ha accepted. So that there is the influence of gymnastics parturition to the strengthening of the abdominal muscles Conclusion : With these results we can conclude there was an effect on muscle strengthening exercises postpartum belly post partum